2017
DOI: 10.1016/j.nano.2017.03.010
|View full text |Cite
|
Sign up to set email alerts
|

Direct detection of nano-scale extracellular vesicles derived from inflammation-triggered endothelial cells using surface plasmon resonance

Abstract: A major conceptual breakthrough in cell signaling has been the finding of EV as new biomarker shuttles in body fluids. Now, one of the major challenges in using these nanometer-sized biological entities as diagnostic marker is the development of translational methodologies to profile them. SPR offers a promising label-free and real time platform with a high potential for biomarker detection. Therefore, we aimed to develop a uniform SPR methodology to detect specific surface markers on EV derived from patient w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
37
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

4
4

Authors

Journals

citations
Cited by 35 publications
(42 citation statements)
references
References 24 publications
5
37
0
Order By: Relevance
“…UC-purified EV contained a mixture of large (microvesicles) and small EV (exosomes) (TEM image: Figure 1 A and NTA analysis: Figure S1 in Supplementary Material). In line with previous data, UC-isolated EV from either untreated EC (uEV) or EC treated with TNF-α (tEV) were enriched with both classical EV membrane-bound biomarkers including CD9, CD63, CD81, and ICAM-1 ( 16 ). Comparative marker analysis of selected classical (CD9 and CD63) and inflammatory (ICAM-1) associated markers was performed on the bulk of uEV and tEV using western blot.…”
Section: Resultssupporting
confidence: 88%
See 2 more Smart Citations
“…UC-purified EV contained a mixture of large (microvesicles) and small EV (exosomes) (TEM image: Figure 1 A and NTA analysis: Figure S1 in Supplementary Material). In line with previous data, UC-isolated EV from either untreated EC (uEV) or EC treated with TNF-α (tEV) were enriched with both classical EV membrane-bound biomarkers including CD9, CD63, CD81, and ICAM-1 ( 16 ). Comparative marker analysis of selected classical (CD9 and CD63) and inflammatory (ICAM-1) associated markers was performed on the bulk of uEV and tEV using western blot.…”
Section: Resultssupporting
confidence: 88%
“…In our previous study, we already demonstrated that an elevated level of ICAM-1(+) small EV were released from inflammation-triggered EC ( 16 ). To our knowledge, this study presents the first complete overview of the common immunomodulatory content of the combined fraction of both small and large EV released from inflammatory-triggered EC.…”
Section: Discussionmentioning
confidence: 92%
See 1 more Smart Citation
“…Considering the two peaks in the NTA graph, and mean diameter of 171.6 nm, our sample contain heteregoneous mixture of exosome and microvesicles including ectosomes, membrane particles and apoptotic vesicles as a typical result of high-speed ultracentrifugation protocols reported elsewhere 26 , 27 . Therefore, as other biosensor papers in literature 28 , 29 , in this work we will use EVs as a more general term. Similar to other optical 30 and electrochemical biosensors 17 , 24 designed for EVs detection, in our work we assumed that the EVs suspensions are monodisperse with a mean diameter, obtained from the NTA analysis.…”
Section: Resultsmentioning
confidence: 99%
“…A more sophisticated method is surface plasmon resonance spectroscopy, which measures refractory index changes as a result of mass bound to a golden surface under flow conditions. When the surfaces are functionalized with specific antibodies against EV surface markers, EV can be measured specifically within biologic samples, as was recently demonstrated for endothelial EV ( 26 ). Although the above assays have the advantage that they allow the qualitative and specific analysis of EV, the results of BIA may be difficult, if not impossible, to translate to absolute counts and to particle sizes.…”
Section: Isolation and Measurement Of Ev—are We Getting Closer To A Gmentioning
confidence: 96%